Enhancing Teachers' Knowledge of Artificial Intelligence and Information Technology at SMPN 11 Pekanbaru: Penguatan Literasi Teknologi Informasi dan Artificial Intelligence bagi Pendidik SMPN 11 Pekanbaru - Sujana, Teguh; Amalia Putri, Rizka; Nasfianti, Iis; Wulandari, Nindya; Fawrin, Heralda (Jurnal Pengabdian UntukMu NegeRI, 2025)
Rapid technological advancements necessitate that educators constantly adjust to new advances, such as the application of artificial intelligence (AI) and information technology in the classroom. The fact remains that many educators are still not accustomed to incorporating technology into their lessons. By promoting the use of AI as a learning aid and adopting IT-based learning, this community service project seeks to improve the knowledge and abilities of SMPN 11 Pekanbaru instructors. The Participatory Rural Appraisal (PRA) method was used in the activity, which was conducted as a workshop with materials, discussions, and practical application. A variety of applications that can aid in the learning process were presented to the teachers. The activity's outcomes demonstrated a rise in teachers' technological knowledge and proficiency as well as the appearance of motivation to innovate in the classroom. Teachers can better prepare for the difficulties of teaching in the digital age by starting with this activity.